Goat systems of Villuercas-Ibores area in SW Spain: Problems and perspectives of traditional farming systems - Gaspar, P.; Escribano, A. J.; Mesías, F. J.; Escribano, M.; Pulido, A. F. (Small Ruminant Research, 2011)
A study of dairy goat systems was carried out in the “Villuercas-Ibores” region, a mountainous area located in the south-west of the Iberian Peninsula (Cáceres, Spain). This territory is characterized by difﬁcult orography and a fairly harsh climate, and has low indices of income and population density. Goat production in the area has contributed notably to its economic and social development historically, but there has been a marked recession in goat-based activities in recent decades, leading to changes in the type and intensity of land use. The purpose of the study is to analyze the main characteristics of the current goat farming systems in a zone in which goat milk production is possible under a Protected Designation of Origin (PDO) brand “Ibores Cheese”, and to establish a farm classiﬁcation that will allow groups of holdings with common characteristics to be identiﬁed, so that they can be compared and their performance evaluated. The data were obtained through direct interviews to goat farmers (n = 61) within the geographical area of the PDO “Ibores Cheese”. Speciﬁc information on management was collected, together with data on family characteristics, labour, livestock numbers, land use, installations, continuity, recent changes in farming, and the farmer’s opinions. A principal component analysis (PCA) was used to examine the relationships among the quantitative variables, then a two-step cluster analysis was applied using the factors obtained in the PCA and categorical variables. This resulted in a farm typology of three groups distinguished by their land use, goat breed, and PDO membership. The best management practices and productivity results were obtained by the farms furthest removed from the traditional systems. The ﬁrst group of farms is characterized by small size ﬂocks. Many of these farms do not belong to the PDO and therefore they have chosen breeds that are not allowed by the PDO regulations. Most of them are semi-intensive or intensive farms. The second group consist of extensive farms with large size ﬂocks of goats complemented with sheep farming and, occasionally, with beef cattle or Iberian pig. They have got technically suitable milking rooms, although the availability of other infrastructure is poor. Finally, the third group identiﬁed includes extensive farms whose goat ﬂock size is very similar to that of group 1, but in 70% of the cases they are mixed farms, mainly combining goat with sheep ﬂocks. Most of them are producing milk that is sold to ﬁrms producing PDO cheese. It is the group closest to the traditional farming system and the farms have small ﬂocks of low productivity per goat, raising autochthonous breeds and their crossbreeds.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Farm typology; goat systems; Management practices; multivariate analysis; PDO “Ibores Cheese”

Characterization of semi-extensive goat production systems in southern Spain - Castel, J M; Mena, Y; Delgado-Pertinez, M; Camunez, J; Basulto, J; Caravaca, F; Guzman-Guerrero, J L; Alcalde, M J (SMALL RUMINANT RESEARCH, 2003)
This study attempts to describe the semi-extensive goat fanning sector in Andalusia (south of Spain) and to establish characteristics. Eighty-nine goat farmers were surveyed in three areas of this region. The survey examined all aspects of the systems, from socio-economy to management. A multivariate analysis (multiple correspondence and cluster) was used to determine the different farm characteristics. Most of the goat farms studied are single-worker or family managed. The farmers lack training and are elderly, so that continuity of the activity is not assured, although newcomers are usually young. All the farms have some area in ownership, although the farms most specialized in dairy goat products are the smallest in both ownership and total area. The roads are generally in good condition, except on farms with little land, situated in areas of the sierra. Machine-milking installations, closely related to the presence of infrastructures and of goats with a dairy tendency, are generally lacking, (this aspect is improving day by day). Artificial nursing is less generalized than machine-milking. Farms specializing in milk production, whose main activity is dairy goat farming, have dairy specialized breed or crossbred (milk and meat) goats. Feeding depends largely on grazing, with little area being cultivated to produce feed for the goats. Little distinction is made for the production level. Olive or acorn tree branches (Quercus ilex spp.) are used as feedstuff, depending on the types of tree predominating in the area. Five farm types were established, the differences depending on 14 variables of socio-economic aspects, level of production, infrastructure and installations, and feeding. Generated information from this study entails an advance into knowledge of goat farming systems in the Mediterranean area (where little information is generated). The relevance of this study is important since Andalusia has 40% of goats in Spain that produce more than half of the total goat milk in the country, which points out the socio-economical importance for most depressed areas in the region. This work supposes previous steps for improving the semi-extensive goat farming sector. From a methodological point of view, the discussion on variable types and utility establishes farm type characteristics. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: characterization methods; goat systems; semi-extensive farming; southern Spain

Characterization of semi-extensive goat production systems in southern Spain - Castel, J. M.; Mena, Y.; Delgado-Pertinez, M.; Camunez, J.; Basulto, J.; Caravaca, F.; Guzman-Guerrero, J. L.; Alcalde, M. J. (SMALL RUMINANT RESEARCH, 2003)
This study attempts to describe the semi-extensive goat fanning sector in Andalusia (south of Spain) and to establish characteristics. Eighty-nine goat farmers were surveyed in three areas of this region. The survey examined all aspects of the systems, from socio-economy to management. A multivariate analysis (multiple correspondence and cluster) was used to determine the different farm characteristics. Most of the goat farms studied are single-worker or family managed. The farmers lack training and are elderly, so that continuity of the activity is not assured, although newcomers are usually young. All the farms have some area in ownership, although the farms most specialized in dairy goat products are the smallest in both ownership and total area. The roads are generally in good condition, except on farms with little land, situated in areas of the sierra. Machine-milking installations, closely related to the presence of infrastructures and of goats with a dairy tendency, are generally lacking, (this aspect is improving day by day). Artificial nursing is less generalized than machine-milking. Farms specializing in milk production, whose main activity is dairy goat farming, have dairy specialized breed or crossbred (milk and meat) goats. Feeding depends largely on grazing, with little area being cultivated to produce feed for the goats. Little distinction is made for the production level. Olive or acorn tree branches (Quercus ilex spp.) are used as feedstuff, depending on the types of tree predominating in the area. Five farm types were established, the differences depending on 14 variables of socio-economic aspects, level of production, infrastructure and installations, and feeding. Generated information from this study entails an advance into knowledge of goat farming systems in the Mediterranean area (where little information is generated). The relevance of this study is important since Andalusia has 40% of goats in Spain that produce more than half of the total goat milk in the country, which points out the socio-economical importance for most depressed areas in the region. This work supposes previous steps for improving the semi-extensive goat farming sector. From a methodological point of view, the discussion on variable types and utility establishes farm type characteristics. (C) 2002 Elsevier Science B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: characterization methods; goat systems; semi-extensive farming; southern Spain